2014
DOI: 10.4081/ijas.2014.3163
|View full text |Cite
|
Sign up to set email alerts
|

Eggshell Quality, Eggshell Structure and Small Intestinal Histology in Laying Hens Fed Dietary Pantoea-6®and Plant Extracts

Abstract: The present study aims to investigate the effects of dietary ® (extract of fermented wheat flour with Pantoea agglomerans) and plant extracts (red clover and garlic) on eggshell quality and structure and intestinal histology. Sixty-six Boris Brown laying hens (30 weeks old) were allotted to 3 groups, each with eleven replicates of two chickens. The control group was fed a basal diet (18% crude protein, 2850 kcal/kg ME) and the other groups were fed the basal diet supplemented with 0.1% Pantoea-6 ® (including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
5
11
0
Order By: Relevance
“…Plant extracts were further discussed in many studies to investigate their effect on egg quality of the laying hens. In a more recent study on Boris Brown layers, Lokaewmanee et al (2014) cited that dietary plant extracts improved significantly the eggshell quality of strength against breaking, and this positive effect could be attributed to an observed improvement in small-intestine histological parameters. Sharma et al (2009) observed increased eggshell thickness (by 10.0%) and strength against breaking (by 15.2%), as well as decreased number of eggs with shell defects (by 2.5 percentage points) in hens fed diet supplemented with herbal products.…”
Section: Introductionmentioning
confidence: 99%
“…Plant extracts were further discussed in many studies to investigate their effect on egg quality of the laying hens. In a more recent study on Boris Brown layers, Lokaewmanee et al (2014) cited that dietary plant extracts improved significantly the eggshell quality of strength against breaking, and this positive effect could be attributed to an observed improvement in small-intestine histological parameters. Sharma et al (2009) observed increased eggshell thickness (by 10.0%) and strength against breaking (by 15.2%), as well as decreased number of eggs with shell defects (by 2.5 percentage points) in hens fed diet supplemented with herbal products.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of dietary plant extracts added into feed mixture of layers on the content of phosphorus, calcium and magnesium in eggshell were not significant (Lokaewmanee et al, 2014). Herkeľ et al (2016) also reported that phytogenic additive including essential oil may significantly affect mineral composition in poultry products.…”
Section: Resultsmentioning
confidence: 99%
“…Relative to mineral composition, yolks from egg produced by hens fed the control treatment (no oil) were significantly different only from those derived from hens fed the diet supplemented with 2.5% canola oil + 2.5% soybean oil, which presented lower mineral content (Faitarone et al, 2013). The effect of dietary plant extracts added into feed mixture of layers on the content of phosphorus, calcium and magnesium in eggshell were not significant (Lokaewmanee et al, 2014). Herkeľ et al (2016) also reported that phytogenic additive including essential oil may significantly affect mineral composition in poultry products.…”
Section: Mineral Composition Of Egg Massmentioning
confidence: 92%
“…Differences in ALP were not significant. Lokaewmanee et al (2014) researched effect of plant extract addition in diets on blood components of laying hens. Among the dietary treatments were not detected significant differences in content of AST, ALT, ALP and bilirubin.…”
Section: Blood Parameters Of Laying Hensmentioning
confidence: 99%